Causes of Actors Doing Household Abandonment - Fitri Amalia Tine (Estudiante Law Journal, 2023)
The purpose of this research is to know and analyze aboutWhat are the factors that cause the perpetrator to commit household abandonmentin Gorontalo and how are the efforts of the Gorontalo Regional Police in tackling cases of neglect in households in the province of Gorontalo. Based on the study conducted by researchers, it can be concluded thatFactors that cause the occurrence of criminal acts of domestic violence in the form of neglectnamely: 1) The public's lack of understanding of legal rules.2) As a result of the husband remarrying to another woman or a third person. The actions taken by the Gorontalo Regional Police in tackling criminal acts of neglect in the household are: 1) through mediation. 2) preventive or prevention. 3) curative namely through directed and integrated actions